Tortura: de método a crime - Carlos Henrique Alvarenga Urquisa Marques (2014)
This study is focused on identifying the changes brought by humanism to the legal conception of torture. To do so, this work is divided into three parts. The first is aimed at understanding the pre modern reality that torture is a legitimate tool of the system. It then presents the theoretical foundation that is employed by inquisitorial system to justify the use of torture. In the second part of the research, humanist thought is presented. The historical context of its emergence is described to then be shown as humanism criticizes the use of torture. The third and final phase of the research, is used to describe how humanism caused change in the legal systems, leading to a process of criminalization of torture.